Incentive valence differentially engages open- and closed-loop basal ganglia circuits during movement initiation - Neil M. Dundon; Elizabeth J. Rizor; Joanne E. Stasiak; Jingyi Wang; Taylor Li; Kiana Sabugo; Christina Villanueva; Parker Barandon; Viktoriya Babenko; Renee Beverly-Aylwin; Alexandra Stump; Tyler Santander; et al. (Proceedings of the National Academy of Sciences, 2026)
Incentives modulate voluntary movement, yet the circuitry channeling these signals into motor output remains unclear. Classical models emphasize a closed-loop circuit (CLC) linking dorsal putamen (PUTd) with the motor cortex, but this pathway is anatomically segregated from affective processing regions. Anatomical and clinical evidence point to an alternative: an open-loop circuit (OLC) from ventral putamen (PUTv) that may route affective signals to the motor cortex. Here, we conducted two experiments to test whether a functional OLC exists in humans and whether it is differentially engaged by incentive conditions. First, in 7 T resting-state fMRI (multi-echo), PUTv showed robust functional connectivity with both affective and motor regions, including the cingulate motor area, even after accounting for PUTd variance. This connectivity pattern supports the plausibility of an independent pathway linking affective basal ganglia regions to the motor cortex. Second, in 3 T task fMRI (incentivized reaching), jackpot (high-reward) and robber (high-loss avoidance) incentive conditions produced distinct behavioral and neural signatures. Jackpot produced a speed–accuracy trade-off, with faster movement initiation but more false starts. Neurally, this coincided with reduced engagement (BOLD responses relevant for initiation speed) in CLC nodes but not in OLC. Robber, in contrast, eliminated engagement in both OLC and CLC nodes, instead recruiting stopping-related regions (e.g., subthalamic nucleus), consistent with an avoidance phenomenology. Together, these findings support a versatile architecture for movement initiation that flexibly engages distinct cortico-subcortical circuits depending on incentive phenomenology, and offer a candidate mechanism through which affective salience and valence modulate voluntary movement.